Paprastojo suopio (Buteo buteo) veisimosi buveinių pasirinkimo skirtumai ir sąveika su kitais plėšriaisiais paukščiais - Kamarauskaitė, Aušra (Institutional Repository of Vilnius University, 2020)
For forest-dwelling raptors nest sites are the most important recourse for reproduction, but they may be destroyed during forests felling’s. Common Buzzard and Lesser Spotted Eagle (Clanga pomarina) (LSE) breed in similar habitats. Return of the superpredator White-tailed Eagle (Haliaeetus albicilla) (WTE) to ecosystem may induce brood defence behaviour in the mesopredator. The study aim was to investigate the habitat preference of the buzzard, spatio-temporal changes in habitat use and interactions with larger raptors. Eighty nest sites of the buzzard, 47 of LSE in the Kaišiadorys forests and the Biržai forest, 28 buzzard nest sites in years 2017-2018, and 37 in years 2002-2004 in the Kaišiadorys forests, were analysed. The field experiment was performed to determine buzzard brood defence behaviour to WTE. Buzzard habitats between landscapes did not differ only in age of the stands. The plasticity of nest trees and nest sites use was identified within changing landscapes. The Buzzard does not avoid the LSE when choosing nest sites. Habitats of these species differed in the soil humidity of nest stand and in location within forest. The brood defence behaviour towards the WTE is mostly explained by the individual differences of buzzards. Mature stands are the most important component in buzzards breeding habitats. Competition for nest sites between the buzzard and LSE is most likely to happen at the forest edge. Buzzards brood defence behavior was not related with the proximity to the nest sites of WTE.